2018
DOI: 10.3390/s18020607
|View full text |Cite
|
Sign up to set email alerts
|

Flame-Oxidized Stainless-Steel Anode as a Probe in Bioelectrochemical System-Based Biosensors to Monitor the Biochemical Oxygen Demand of Wastewater

Abstract: Biochemical oxygen demand (BOD) is a widely used index of water quality in wastewater treatment; however, conventional measurement methods are time-consuming. In this study, we analyzed a novel flame-oxidized stainless steel anode (FO-SSA) for use as the probe of bioelectrochemical system (BES)-based biosensors to monitor the BOD of treated swine wastewater. A thinner biofilm formed on the FO-SSA compared with that on a common carbon-cloth anode (CCA). The FO-SSA was superior to the CCA in terms of rapid sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The formation of biofilms on various surfaces leads to interesting results. For example, in [ 102 ] it has been shown that a thinner biofilm of microorganisms is formed on a flame-oxidized stainless-steel anode than on a common carbon cloth anode, which improved the performance of MFCs and leads to faster measurements.…”
Section: Immobilization Techniquesmentioning
confidence: 99%
“…The formation of biofilms on various surfaces leads to interesting results. For example, in [ 102 ] it has been shown that a thinner biofilm of microorganisms is formed on a flame-oxidized stainless-steel anode than on a common carbon cloth anode, which improved the performance of MFCs and leads to faster measurements.…”
Section: Immobilization Techniquesmentioning
confidence: 99%
“…As a result, the developed biosensor offered better performance than traditional carbon-cloth anodes in bioelectrochemical biosensors. The authors further proposed various practical utilizations of the biosensor to improve the biomonitoring of wastewater (Liang et al 2018 ). The great challenge nowadays is the monitoring of the marine environment.…”
Section: Advances and Potential Applications Of Biosensorsmentioning
confidence: 99%
“…Liang, Yamashita, Yamamoto‐Ikemoto, and Yokoyama (2018) analyzed a flame‐oxidized stainless steel anode (FO‐SSA) and used as the probe of bioelectrochemical system (BES)‐based biosensors to monitor the biochemical oxygen demand (BOD) of treated swine wastewater. The FO‐SSA was superior to the CCA in terms of rapid sensing and offered better performance than traditional CCAs in BES biosensors.…”
Section: Instrumentationmentioning
confidence: 99%